The Contribution of Street Libraries in Australia to Literacy, Community and the Gift Economy. Issue 1 (2nd January 2022) - Chen, Peter John
ABSTRACT: This paper examines the phenomenon of Australian 'street libraries'. Enthusiasts have suggested that they contribute to their communal fabric, providing increased sociability and promoting reading and literacy. Street libraries have been associated with 'placemaking' activities. Seen as part of the 'gift' economy, their 'Take a book. Give a Book. Share a Book.' motto promotes their role in recycling. International research has contested some of these claims, with some critics suggesting their role in addressing 'book deserts' is limited, that they represent a highly individualised paternalism by social and economic elites, and they are associated with the neoliberal assault on public libraries. This paper finds mixed evidence in support for the views of advocates and critics. Australian street libraries are skewed towards localities with the highest socio-economic measures of advantage. They are less 'interventions' into the landscape, as associated with private ownership. Street librarians are not, however, disproportionately urban, and their maintainers have greater economic diversity than their 'elite' characterisation would imply. Street libraries can be seen as an example of a gift economy, recycling about $11 million in value in 2021. In addition, some social capital advantages in establishing and maintaining a street library can be identified.